2012
DOI: 10.1186/2047-2994-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin exposure precedes infection and/or colonization with daptomycin non-susceptible enterococcus

Abstract: BackgroundDaptomycin non-susceptible enterococci (DNSE) are emerging as an important cause of healthcare-associated infection, however little is known about the epidemiology of DNSE. At the University of Iowa Hospitals and Clinics (UIHC) an increase in the frequency of patients infected and/or colonized with DNSE has occurred. The goals of this study were to evaluate potential factors associated with the development of DNSE colonization and/or infection and to compare the characteristics of patients with prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
25
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 18 publications
7
25
1
Order By: Relevance
“…Daptomycin-nonsusceptible enterococci, however, are emerging as a cause of health careassociated infection (4,6) and may be fairly common; they comprised 3.9% of 2,029 Enterococcus faecium isolates from U.S. hospitals over the period 2007 to 2010 (13) and 15.2% among VRE blood isolates at a New York cancer center (14). In addition to some earlier case reports (reviewed in reference 4), a notable increase in the number of patients infected or colonized with daptomycin-nonsusceptible enterococci has been reported from different geographic regions in the United States (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Daptomycin-nonsusceptible enterococci, however, are emerging as a cause of health careassociated infection (4,6) and may be fairly common; they comprised 3.9% of 2,029 Enterococcus faecium isolates from U.S. hospitals over the period 2007 to 2010 (13) and 15.2% among VRE blood isolates at a New York cancer center (14). In addition to some earlier case reports (reviewed in reference 4), a notable increase in the number of patients infected or colonized with daptomycin-nonsusceptible enterococci has been reported from different geographic regions in the United States (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Most patients develop resistance during daptomycin therapy (18,20,21). De novo resistance is also reported for some patients without prior use of daptomycin (16,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While DAP susceptibility among enterococci remains Ͼ99%, continued use of DAP will likely increase the frequency of resistance worldwide (12). Several studies have already reported the development of resistance in both S. aureus (6,(13)(14)(15)(16) and enterococci (2,(17)(18)(19). Recent evidence strongly suggests that DAP inserts into the plasma membrane in a calcium-dependent manner and subsequently disrupts the functional integrity of the cell membrane, altering cell division.…”
mentioning
confidence: 99%
“…nterococci are important pathogens responsible for serious infections, such as urinary tract infections, bacteremia, skin and soft tissue infections, endocarditis, and meningitis, and they are a major contributor to nosocomial infections in the United States (1,2). Enterococcus faecalis and E. faecium are responsible for the majority of clinical infections, and their treatment has become increasingly problematic as more than 80% of E. faecium isolates are now resistant to ampicillin and vancomycin (1).…”
mentioning
confidence: 99%